A cofuel channel microtubular solid oxide fuel/electrolysis cell. (1st December 2022) - Yao, Yue; Ma, Yue; Wang, Chenpeng; Ye, Hao; Liu, Yinglong; Liu, Jiawei; Zhao, Xiaobo; Tao, Tao; Yao, Yingbang; Lu, Shengguo; Yang, Huazheng; Liang, Bo
Highlights: Co-fuel channel microtubular SOFC/SOEC with the same diameter are successfully tested. SOEC/SOFC simultaneously achieve 1.0 A cm −2 at 1.7 V and 0.6 A cm −2 at 0.6 V. The anode-electrolyte interface structure lacks Ni agglomeration and active phase loss. Abstract: A co-fuel channel microtubular solid oxide fuel/electrolysis cell is successfully fabricated by adding an insulating ceramic connector. The active electrode area of both of the abovementioned cells is approximately 10.73 cm 2 . Hydrogen-steam mixtures act as either reactants or products in the ceramic tubes. A ring-like anodic current collector is located in the middle of the anode, while silver paste is coated on the cathode as a cathodic current collector. When operating the cells at 750 ℃, 0.6 A cm −2 at 0.6 V and 1.0 A cm −2 at 1.7 V are achieved for the SOFC and SOEC, respectively. By using the co-fuel channel, the power generation of the SOFC is 3.9 W, while the simultaneous power consumption of the SOEC is 18.2 W. After 11 h of operation, no microcracks were observed, and the anode-electrolyte interface structure exhibited no Ni agglomeration or active phase loss.